The Influence of Education Level and Coding Bootcamp, Through Competency and Its Impact on IT Personnel Performance - Sutardiyanta, Ihwan; Sobandi, Ade (Universitas Ibn Khladun Bogor, 2024)
This study aims to analyze the effect of Level of Education and Coding Bootcamp on Competency and its impact on IT Personnel Performance. The population of this study is IT Engineers who work in several companies with a sample size of 80 respondents. The data collection method used was a questionnaire. The data analysis technique uses PLS-SEM. The results showed that directly, Level of Education has no significant effect on Competency, Coding Bootcamp has a positive and significant effect on Competency, Level of Education has no significant effect on Performance, Coding Bootcamp has a positive and significant effect on Performance, Competency has a positive and significant effect on Performance and Competency variables mediate between Level of Education and Coding Bootcamp variables on IT Personnel Performance.